'This slot is hotter than that one': symbolic generalization of slot machine preference in simulated gambling. Issue 3 (2nd September 2019) - Hoon, Alice E.; Bickford, Craig; Samuels, Lotte; Dymond, Simon
ABSTRACT: Slot-machine choice may be influenced by structural features like display labels, independent of the programmed payout probability. Gambling choice may then involve verbal descriptions or rules comparing machines based on structural characteristics such as "this one is better than another. This study developed an experimental analogue examining how display labels influences choices in simulated slot-machine gambling. Eighty-eight participants learned a relational series of arbitrary nonsense words that were either 'more-than' (E > D > C > B > A) or 'less-than' (A < B < C < D < E). Participants were then exposed to a slot-machine payout probability phase to establish one machine, labelled with the middle-ranking word, C, as having a low likelihood of winning. Another machine, labelled with a novel word, X, had a high likelihood of winning. In the test phase, participants were given choices of slot-machines labelled with all remaining nonsense words. It was predicted that slot-machine choices would be influenced by the underlying relational hierarchy of nonsense words. Findings supported this, with choices showing a gradient-like pattern, despite no prior experience with the payout probabilities. This suggests that slot-machine choices could be influenced by structural properties, and not just payout probability.